Pengaruh Pelatihan, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja Pegawai pada PT Kappa Carrageenan Nusantara Pasuruan - Edwin Adha Mulia; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine whether the effect of training, work discipline and employee work environment partially and simultaneously has an effect on employee performance. This research was conducted at PT Kappa Carrageenan Nusantara Pasuruan with a population and sample of 97 employees. The type of research used is quantitative research. The data analysis method in this study used statistical analysis with the SPSS program. The results showed that training, work discipline, and work environment simultaneously had an effect on employee performance, while partially training, work discipline, and work environment had a significant effect on employee performance at PT Kappa Carrageenan Nusantara Pasuruan. Contributions in this study can be an evaluation for interested parties in the company PT KCP Pasuruan should pay attention to the factors in this study for the creation of better employee performance.Keywords: Training, Work Discipline, Work Environment, and Employee Performance